Normalizing Dirty Work: Managerial Tactics For Countering Occupational Taint - E. Ashforth, Blake; E. Kreiner, Glen; A. Clark, Mark; Fugate, Mel (Academy of Management Journal, 2007)
Dirty work refers to occupations that are viewed by society as physically, socially, or morally tainted. Using exploratory, semistructured interviews with managers from 18 dirty work occupations, we investigated the challenges of being a manager in tainted work and how managers normalize taint–that is, actively counter it or render it less salient. Managers reported experiencing role complexity and stigma awareness. Four types of practices for countering taint were revealed: occupational ideologies, social buffers, confronting clients and the public, and defensive tactics. We discuss links between these practices.